2014
DOI: 10.1159/000366333
|View full text |Cite
|
Sign up to set email alerts
|

The MBD4 Gene Plays an Important Role in Porcine Adipocyte Differentiation

Abstract: Background: MBD4 (methyl-CpG binding domain protein 4) is an important G: T glycosylase that can identify T-G mismatches. It plays a role in active demethylation through base excision repair. Overexpression of MBD4 gene can cause the demethylation of numerous genes, and the remethylation of MBD4-associated genes can occur when the MBD4 gene is knocked out. To date, the functions and regulatory mechanisms of the MBD4 gene in the differentiation of porcine preadipocytes have not been clearly established. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The cells were then washed twice with PBS, stained with 10% Oil Red O solution (solvent: 70% ethanol) for 15 min, decolorized rapidly in 75% ethanol, and washed twice with PBS. Subsequently, the cells were counterstained with hematoxylin for 15 s and washed three times with PBS . The stained cells were observed under a microscope and photographed.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were then washed twice with PBS, stained with 10% Oil Red O solution (solvent: 70% ethanol) for 15 min, decolorized rapidly in 75% ethanol, and washed twice with PBS. Subsequently, the cells were counterstained with hematoxylin for 15 s and washed three times with PBS . The stained cells were observed under a microscope and photographed.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction system was as follows: 0.5 μl (10 pmol/L) of upstream primer, 0.5 μl (10 pmol/L) of downstream primer, 8.0 μl of ddH 2 O, 1 μl of template and 10 μl of SYBR R Premix Ex Taq II (2x), with the following conditions: 95°C for 30 s; and 40 cycles of 95°C for 5 s and 60 °C for 30 s. The U6 small nuclear RNA (snRNA) was used as an internal control for miR-378, and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as an internal control for other genes. Experimental data were analyzed using a relative quantification method (2 [16,17].…”
Section: Rna Extraction and Quantitative Real-time Reverse Transcriptmentioning
confidence: 99%
“…Previous studies recommended that DNMT3A inhibited porcine intramuscular preadipocytes differentiation by changing the methylation levels of p21 and PPARγ (Abdalla et al, 2018;Qimuge et al, 2019). Zhang et al (2014) found that MBD4 inhibited porcine preadipocytes differentiation by changing the DNA methylation levels of adipogenic genes. Li et al suggested that DNA methylation regulated chicken PPARG and CEBPA during the development of chicken adipose tissue (Sun et al, 2014;Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 96%